LSD1 Promotes Prostate Cancer Cell Survival by Destabilizing FBXW7 at Post-Translational Level - Qin, Xu-ke; Du, Yang; Liu, Xiu-heng; Wang, Lei (Frontiers in Oncology, 2021)
Prostate cancer (PCa) is the most common cancer in men and the fifth leading cause of cancer death worldwide. Unfortunately, castration-resistant prostate cancer (CRPCa) is incurable with surgical treat and prone to drug resistance. Therefore, it is of great importance to find a new target for treatment. LSD1 is up-regulated in PCa and related with prognosis. The high-expression LSD1 has been shown to be a potential target for treatment and is widely studied for its demethylase-activity. However, its demethylation-independent function remains to be elusive in PCa. Recent study shows that LSD1 can destabilize cancer suppressor protein FBXW7 without demethylation-function. Hence, we hope to investigate the impact of noncanonical function of LSD1 on PCa cell survival. We over-expressed FBXW7 gene through plasmid vector in LNCaP and PC3 cell lines and the result shows that up-regulated FBXW7 can suppress the viability of PC cell through suppressing oncoproteins, such as c-MYC, NOTCH-1. After FBXW7 function experiment on PC cell, we knock-down LSD1 gene in the same kinds of cell lines. In western blot assay, we detected that down-regulation of LSD1 will cause the increasing of FBXW7 protein level and decreasing of its targeting oncoproteins. And mRNA level of FBXW7 did not change significantly after LSD1 knock-down, which means LSD1 may destabilize FBXW7 by protein-protein interactions. Moreover, exogenous wild type LSD1 and catalytically deficient mutant K661A both can abrogate previous effect of LSD1 knock-down. Consequently, LSD1 may promote PC cell survival by destabilizing FBXW7 without its demethylase-activity. Next, we compared two kinds inhibitors, and found that SP-2509(Allosteric inhibitor) treatment suppress the cancer cell survival by blocking the LSD1–FBXW7 interaction, which is an effect that GSK-2879552 (catalytic inhibitor) cannot achieve. This work revealed a pivotal function of LSD1 in PCa, and indicated a new direction of LSD1 inhibitor research for PCa treatment.